2019
DOI: 10.1111/nph.16067
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution computed tomography reveals dynamics of desiccation and rehydration in fern petioles of a desiccation‐tolerant fern

Abstract: Summary Desiccation‐tolerant (DT) plants can dry past −100 MPa and subsequently recover function upon rehydration. Vascular DT plants face the unique challenges of desiccating and rehydrating complex tissues without causing structural damage. However, these dynamics have not been studied in intact DT plants. We used high resolution micro‐computed tomography (microCT), light microscopy, and fluorescence microscopy to characterize the dynamics of tissue desiccation and rehydration in petioles (stipes) of intac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
(59 reference statements)
2
22
0
Order By: Relevance
“…Here we demonstrate that considerable (up to 80%) reductions in K shoot in two Selaginella species precede embolism formation. Visualization of the internal anatomy of the stem by micro-CT revealed that, similar to desiccation-tolerant ferns (Holmlund et al, 2019), a physical separation between the cortex and the vascular cylinder occurred when Ψ declines in Selaginella. Unlike in desiccation-tolerant ferns, the large, air- filled lacuna in Selaginellaforms at high Ψ before embolism formation and is the result of water loss and cell collapse in the cortex, not from the vascular tissue collapsing within the vascular cylinder.…”
Section: Declines In Hydraulic Conductance and Embolism Formationmentioning
confidence: 99%
“…Here we demonstrate that considerable (up to 80%) reductions in K shoot in two Selaginella species precede embolism formation. Visualization of the internal anatomy of the stem by micro-CT revealed that, similar to desiccation-tolerant ferns (Holmlund et al, 2019), a physical separation between the cortex and the vascular cylinder occurred when Ψ declines in Selaginella. Unlike in desiccation-tolerant ferns, the large, air- filled lacuna in Selaginellaforms at high Ψ before embolism formation and is the result of water loss and cell collapse in the cortex, not from the vascular tissue collapsing within the vascular cylinder.…”
Section: Declines In Hydraulic Conductance and Embolism Formationmentioning
confidence: 99%
“…Most ferns are not well adapted to water deficit, but studies have indicated that variation in species drought tolerance is consistent with habitat and species life history strategy (Watkins et al, 2010;Burns et al, 2016;Holmlund et al, 2016Holmlund et al, , 2019Holmlund et al, , 2020. Drought tolerance in plants is linked to cavitation resistance, that is the degree to which the xylem is susceptible to dysfunction by air entry.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Also, these compounds have been utilized for the spatial, in-vivo, dynamic visualization of water movement in roots [20] or conductive conduits (xylem) during tissue desiccation/rehydration, embolism resistance [21] and repair. [22] Interestingly, the combination of CT and non-radioactive, metabolizing iodinated glucose 2-deoxy-2-iodo-D-glucose (DIG) for exploring sugar transport and accumulation in smaller plants still remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%